2022
DOI: 10.1016/j.jaim.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Ayurvedic management of persistent hypoxia in a diabetic and hypertensive COVID-19 patient in the post-hospitalization period–A case report

Abstract: Introduction Low oxygen saturation may persist in COVID-19 patients even after hospital discharge, requiring continued supplemental oxygen therapy at home. In this paper, we report the significant benefits of add on Ayurvedic intervention as observed in an oxygen dependent COVID-19 patient in the post hospitalization period. Main symptoms and important clinical findings : A 75-year-old gentleman approached his Ayurvedic general practitioner with complaints of low oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The article lists specific herbs and formulations that may be used to treat patients in each category and recommends adjusting the dosage of individual formulations based on the patient's strength and the severity of the disease. Other studies have suggested that Ayurvedic care may be a cost-effective first-line treatment in an integrative setting for patients with persistent hypoxia in the post-hospitalization phase [ 67 , 68 ]. A machine-based topic modeling study found that messages about “Yoga and Ayurveda for immunity” had a significant herd effect [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The article lists specific herbs and formulations that may be used to treat patients in each category and recommends adjusting the dosage of individual formulations based on the patient's strength and the severity of the disease. Other studies have suggested that Ayurvedic care may be a cost-effective first-line treatment in an integrative setting for patients with persistent hypoxia in the post-hospitalization phase [ 67 , 68 ]. A machine-based topic modeling study found that messages about “Yoga and Ayurveda for immunity” had a significant herd effect [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the hypoxia case presented by Jyoti Joshi et al. [ 42 ] the 75-year COVID-19 with CO-RADS 6, 18/25 who underwent ICU care for 16 days with SpO2 between 80 and 85 oxygen dependent even after discharge with increased covid biomarkers-the oxygen saturation improved to 95 in 12 h of initiating ayurvedic treatment, oxygen support was weaned off on the third day. Complete clinical recovery along with reversal of most biomarkers related to the disease severity within 19 days of initiation of Ayurveda intervention; totally 35 days of treatment was required.…”
Section: Discussionmentioning
confidence: 99%